PENEMPATAN KERJA DAN MOTIVASI SERTA IKLIM ORGANISASI DALAM MEMPENGARUHI KINERJA KARYAWAN PT. SUCOFINDO (PERSERO) WILAYAH SUMATERA SELATAN-BANGKA BELITUNG. - Emelda Emelda (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2018)
The purpose of the study was to determine the effect and motivation of employee work on the performance of PT. Sucofindo (Persero) South Sumatra Region - Bangka Belitung. The problem is what is meant by work placement and motivation and corporate climate simultaneously and partially on the performance of employees of PT. Sucofindo (Persero) South Sumatra Region - Bangka Belitung. The sample in this study were 101 people. The results of the study show that simultaneously and partially there are contributions to the placement, motivation and climate of the organization on the performance of the employees of PT. Sucofindo (Persero) South Sumatra Region - Bangka Belitung.